Pengembangan media pembelajaran berbasis web google sites pada materi ikatan ion dan kovalen untuk SMA kelas X - Sitepu, Deri Salsalina Br; Herlinawati, Herlinawati (Educenter : Jurnal Ilmiah Pendidikan, 2022)
In a transition period like now technology is needed in the learning process, teachers must be able to use learning media by utilizing existing technology that makes it easier for students to learn in observations that have been carried out in high school in learning chemistry, it can be seen that during learning the teacher does not use technology in learning. , teachers still use media in the form of textbooks, and give assignments so as to make learning less interesting for students and sometimes make students less understanding of the content of the learning material, the purpose of this research is to analyze the development of web-based learning media google sites developed on subjects chemistry, and the feasibility of the developed google sites web-based learning media. The research and development model of learning media based on the google sites web uses the ADDIE learning model. This study uses non-test instruments, non-test instruments in the form of validation sheets that have met BSNP standards, namely aspects of the feasibility of content, presentation, language and graphics by a four-category scale validator. The results of the feasibility validation show that the development of learning media for google sites on ionic and covalent bonding material is in the feasible category and does not need to be revised with the acquisition of an average content feasibility value of 3.63; language eligibility of 3.85 ; presentation feasibility of 3.87; and the feasibility of the graphic is 3.74.